Risk Factors for Tailor Workers with the Incident of Flak Pain at PT X - Dewi Zuniawati (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Flank pain is a type of problem in the musculoskeletal system. This condition causes pain that appears both on the right and on the left, behind the waist, precisely in the area below the ribs and above the pelvis. Back pain is still a problem from the decline in work productivity in various parts of the world. The purpose of this study is to analyze job risk factors, namely length of sitting, sitting position, and length of work and to find the most influential occupational risk factors among the 3 variables. Research method Quantitative research design through a "cross sectional" approach. This researcher uses Simple Random Sampling with obtained as many as 155 respondents. The data analysis technique uses the Logistic Regression test. The results of this study note that the factor of sitting too long is the most influential factor in the incidence of "flank pain". The results showed that of the 155 respondents who were studied by the researchers, 132 respondents (85%) experienced Flak pain. Respondents with a long duration of sitting > 9 hours were 134 respondents (84%), most of the respondents were in a non-ergonomic sitting position of 132 respondents (92%), as many as 100 respondents (59%) had worked > 10 years. Based on the Logistic Regression test based on the omnibus model test, it shows a significance value of p-value = 0.000 <α = 0.05, meaning that H0 is rejected and H1 is accepted, this means that there is a joint effect between the factors of length of work, length of sitting and duration of work on the incidence of flak pain on Toilor at PT X. . Based on the Exp (B) value with the highest Exp (B) value. ) namely 15,808, it can be concluded that the factor that most influences the incidence of flak pain is long sitting. There is a joint influence of long sitting, sitting position, and length of work with the incidence of Flak Pain in Tailors at PT X and It was found that the most dominant factor influencing the incidence of Flak Pain in Tailor workers was long sitting.